2012
DOI: 10.4236/ijcm.2012.36095
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Efficacy of Foley Catheter Balloon with Dinoprostone Gel for Cervical Ripening at Term

Abstract: Objective: The purpose of this study was to compare the efficacy of extra-amniotic Foley catheter with intra cervical Dinoprostone gel for preinduction cervical ripening. Study Design: A randomized, prospective study was conducted in the Department of Obstetrics and Gynecology, PGIMS Rohtak on 100 pregnant women admitted for induction of labor. Fifty patients were randomized to receive Dinoprostone gel and 50 patients to receive intracervical, extra-amniotic Foley catheter. Results: The two groups were compara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 11 publications
5
10
0
Order By: Relevance
“…Although there was no statistically significant difference in the adverse events reported quantitatively, events like uterine hyper stimulation and hypertonus were reported only in the dinoprostone group while premature rupture of membranes was reported only in Foleys catheter group. 17 Another study conducted at Rothak also shows that only patients in the dinoprostone group experienced hyperstimulation. [17] Difference in pharmacodynamics of Foleys catheter and PGE2 gel may partly explain the qualitative difference observed in type of adverse events.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Although there was no statistically significant difference in the adverse events reported quantitatively, events like uterine hyper stimulation and hypertonus were reported only in the dinoprostone group while premature rupture of membranes was reported only in Foleys catheter group. 17 Another study conducted at Rothak also shows that only patients in the dinoprostone group experienced hyperstimulation. [17] Difference in pharmacodynamics of Foleys catheter and PGE2 gel may partly explain the qualitative difference observed in type of adverse events.…”
Section: Discussionmentioning
confidence: 96%
“…17 Another study conducted at Rothak also shows that only patients in the dinoprostone group experienced hyperstimulation. [17] Difference in pharmacodynamics of Foleys catheter and PGE2 gel may partly explain the qualitative difference observed in type of adverse events.…”
Section: Discussionmentioning
confidence: 96%
“…Krishna Dahiya et al found no difference between the 2 groups in terms of induction to delivery interval and mode of delivery. 13 Sciscione et al No difference between the 2 groups was noted in terms of mode of delivery, infant weight, rate of hyper stimulation, shoulder dystocia, patient discomfort, epidural use, oxytocin use or non-reassuring fetal heart pattern. 14 The only complication noted was fetal distress in both the groups which constituted 25.97% and 13.33% in Foley's and Dinoprostone gel group respectively.…”
Section: Reshme N Et Al Int J Reprod Contracept Obstet Gynecol 2017mentioning
confidence: 98%
“…9,10 Rabindranath et al obtained better results with Foley's catheter labour induction. 11 In a randomised prospective study on 200 patients by Deshmukh et al 12 the change in Bishop Score at the end of 6 hours was 5.56±1.89 and 5.49±1.82 with p value <0.001 for Foley's catheter and Dinoprostone group respectively, which was significant in itself but no difference was found between the 2 groups.…”
Section: Reshme N Et Al Int J Reprod Contracept Obstet Gynecol 2017mentioning
confidence: 99%
See 1 more Smart Citation